The role of cofeeding arthropods in the transmission of Rickettsia felis. - Chanida Fongsaran; Krit Jirakanwisal; Natthida Tongluan; Allison Latour; Sean Healy; Rebecca C Christofferson; Kevin R Macaluso (Public Library of Science (PLoS), 2022)
Rickettsia felis is an emerging etiological agent of rickettsioses worldwide. The cosmopolitan cat flea (Ctenocephalides felis) is the primary vector of R. felis, but R. felis has also been reported in other species of hematophagous arthropods including ticks and mosquitoes. Canines can serve as a bacteremic host to infect fleas under laboratory conditions, yet isolation of R. felis from the blood of a vertebrate host in nature has not been realized. Cofeeding transmission is an efficient mechanism for transmitting rickettsiae between infected and uninfected fleas; however, the mechanism of transmission among different orders and classes of arthropods is not known. The potential for R. felis transmission between infected fleas and tick (Dermacentor variabilis) and mosquito (Anopheles quadrimaculatus) hosts was examined via cofeeding bioassays. Donor cat fleas infected with R. felis transmitted the agent to naïve D. variabilis nymphs via cofeeding on a rat host. Subsequent transstadial transmission of R. felis from the engorged nymphs to the adult ticks was observed with reduced prevalence in adult ticks. Using an artificial host system, An. quadrimaculatus exposed to a R. felis-infected blood meal acquired rickettsiae and maintained infection over 12 days post-exposure (dpe). Similar to ticks, mosquitoes were able to acquire R. felis while cofeeding with infected cat fleas on rats infection persisting in the mosquito for up to 3 dpe. The results indicate R. felis-infected cat fleas can transmit rickettsiae to both ticks and mosquitoes via cofeeding on a vertebrate host, thus providing a potential avenue for the diversity of R. felis-infected arthropods in nature.